Method for producing cellooligosaccharide-containing composition and cellooligosaccharide-containing composition

JP7631954B2Active Publication Date: 2025-02-19RESONAC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021048683
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-02-19
Estimated Expiration
2041-03-23

AI Technical Summary

Benefits of technology

【0017】 本発明のセロオリゴ糖含有組成物の製造方法によれば、比較的重合度が高くても(重合度が3~6)、保存安定性に優れたセロオリゴ糖含有組成物を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631954000006
    Figure 0007631954000006
  • Figure 0007631954000007
    Figure 0007631954000007
  • Figure 0007631954000008
    Figure 0007631954000008
Patent Text Reader

Abstract

To provide a method for producing compositions of cellooligosaccharide excellent in storage stability.SOLUTION: Disclosed is a method for producing a composition comprising cellooligosaccharide, the method comprising hydrolyzing a raw material mixture containing cellulose and xylan in the presence of an acid catalyst, where the content of xylan in the raw material mixture is 5-50 mass% of the total content of cellulose and xylan (100%).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a cellooligosaccharide-containing composition and a cellooligosaccharide-containing composition. [Background technology]

[0002] Cellooligosaccharides are oligosaccharides formed by the polymerization of glucose units through β-1,4 bonds. In recent years, they have been found to have functions such as moisture retention, suppression of stickiness, imparting a clean taste, reducing starch retrogradation, and inhibiting protein denaturation, and are expected to be used in the fields of medicine, cosmetics, food, and feed.

[0003] In particular, cellooligosaccharides with a glucose polymerization degree of 3 or more are expected to have the above-mentioned increased functionality and to provide new functionalities.

[0004] Cellooligosaccharides currently used industrially are produced by enzymatic reactions, and their main components are glucose and the dimer cellobiose (Patent Document 1).

[0005] Known cellooligosaccharide production techniques other than the enzymatic method include a hydrothermal treatment method (Patent Documents 2 to 4) and a hydrothermal treatment method using oxidized water containing hypochlorous acid (Patent Document 5). In both patent documents, cellooligosaccharides are treated as intermediate products in the process of decomposing cellulose into glucose.

[0006] In addition, a method is also known in which a carbon catalyst and cellulose are mixed and crushed, and then hydrolyzed by a hydrothermal synthesis method, and a production method is disclosed in which cellooligosaccharides containing oligomers with a degree of glucose polymerization of up to 6 are obtained (Patent Document 6).

[0007] A method is also known in which cellulose is partially hydrolyzed using a phosphoric acid catalyst by semi-dry conversion (Non-Patent Document 1). This method has a relatively high selectivity and is capable of obtaining cellooligosaccharides with a degree of polymerization of 7 or more.

[0008] However, the methods described in Patent Documents 1 to 5 were not efficient methods for obtaining cellooligosaccharides because the hydrolysis reaction proceeded too far up to glucose. The method described in Patent Document 6 was not efficient as a method for obtaining cellooligosaccharides with a relatively high degree of polymerization because the hydrolysis reaction proceeded up to glucose when an attempt was made to increase the cellulose conversion rate, and temperature control had to be performed very precisely in order to increase the yield of cellooligosaccharides. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2009-189293 A [Patent Document 2] JP 2011-068578 A [Patent Document 3] International Publication No. 2011 / 036955 [Patent Document 4] International Publication No. 2012 / 128055 [Patent Document 5] JP 2006-320261 A [Patent Document 6] International Publication No. 2017 / 104687 [Non-patent literature]

[0010] [Non-Patent Document 1] Bull.Chem.Soc.Jpn.2020,93,273-278 Summary of the Invention [Problem to be solved by the invention]

[0011] On the other hand, in the production methods that produce cellooligosaccharides with a relatively high degree of polymerization (e.g., the method described in Non-Patent Document 1), the resulting cellooligosaccharides have the disadvantages of being insufficiently soluble in water, tending to precipitate during long-term storage, and having poor storage stability.

[0012] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing a cellooligosaccharide-containing composition that has excellent storage stability even when it has a relatively high degree of polymerization. [Means for solving the problem]

[0013] The present inventors have conducted extensive research to solve the above problems and have come up with the idea of ​​using cellulose containing a specific proportion of xylan as a raw material and carrying out hydrolysis in the presence of an acid catalyst.

[0014] As a result, they discovered a method for producing a cellooligosaccharide-containing composition, in which a mixture containing cellulose and xylan, in which the xylan content is 5 to 50 mass% relative to the total content of the cellulose and xylan (100 mass%), is hydrolyzed in the presence of an acid catalyst.

[0015] That is, the present invention includes the following [1] to [8].

[0016] [1] A method for producing a cellooligosaccharide-containing composition, comprising hydrolyzing a raw material mixture containing cellulose and xylan in the presence of an acid catalyst, wherein the raw material mixture contains 5 to 50% by mass of the xylan relative to 100% by mass of the total content of the cellulose and the xylan. [2] The method for producing a cellooligosaccharide-containing composition according to [1], wherein the raw material mixture contains 7 to 40% by mass of the xylan relative to 100% by mass of the total content of the cellulose and the xylan. [3] The method for producing a cellooligosaccharide-containing composition according to either [1] or [2], wherein the acid catalyst is at least one acid or a partially neutralized salt thereof selected from the group consisting of sulfuric acid, sulfurous acid, hydrochloric acid, perchloric acid, nitric acid, nitrous acid, and phosphoric acid. [4] The method for producing a cellooligosaccharide-containing composition according to [3], wherein the acid catalyst is phosphoric acid or a partially neutralized salt thereof. [5] The method for producing a cellooligosaccharide-containing composition according to [4], wherein the acid catalyst is phosphoric acid. [6] A method for producing a cellooligosaccharide-containing composition according to any one of [1] to [5], comprising hydrolyzing the raw material mixture by grinding in the presence of the acid catalyst. [7] The method for producing a cellooligosaccharide-containing composition described in [6], wherein the grinding treatment is carried out using a planetary ball mill or a vibration mill. [8] A cellooligosaccharide-containing composition produced by hydrolyzing a raw material mixture containing cellulose and xylan, the xylan content of which is 5 to 50 mass% relative to 100 mass% of the total content of the cellulose and the xylan. Effect of the Invention

[0017] According to the method for producing a cellooligosaccharide-containing composition of the present invention, a cellooligosaccharide-containing composition having excellent storage stability can be produced even if the degree of polymerization is relatively high (degree of polymerization is 3 to 6). [Brief description of the drawings]

[0018] [Figure 1] 1 is a 1H-NMR chart of the hydrolysate produced in Example 1. [Diagram 2] 1H-NMR chart of the hydrolysate produced in Example 2. [Diagram 3] 1 is a 1H-NMR chart of the hydrolysate produced in Comparative Example 1. [Figure 4] 1H-NMR chart of the hydrolysate produced in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, embodiments of the present invention will be described. Note that the embodiments described below are representative examples of the present invention, and the present invention is not limited thereto.

[0020] In one embodiment, a method for producing a cellooligosaccharide-containing composition includes hydrolyzing a raw material mixture containing cellulose and xylan in the presence of an acid catalyst, and is characterized in that the raw material mixture contains 5 to 50% by mass of the xylan relative to a total content of the cellulose and the xylan of 100% by mass.

[0021] <Raw material mixture> In one embodiment of the method for producing a cellooligosaccharide-containing composition, a raw material mixture containing cellulose and xylan is used as a raw material (hereinafter, may be referred to as a "cellulose-xylan mixture").

[0022] Cellulose and xylan are known as biomass, which is an organic resource derived from plants rather than fossil resources.

[0023] Examples of cellulosic biomass include woody biomass such as cotton, wood pulp, kenaf, hemp, small diameter trees, thinned wood, sawdust, wood chips, waste paper, newspapers, wrapping paper, tissue paper, toilet paper, and cardboard; and herbaceous biomass such as bagasse, switchgrass, elephant grass, corn cobs, rice straw, and wheat straw. These can be used alone or in combination of two or more. For example, water-insoluble cellulose can be used, which is obtained by bleaching these biomasses with chlorine treatment to produce chemical pulp (holocellulose) and then treating this chemical pulp with alkali to remove hemicellulose.

[0024] Generally, cellulose exhibits crystallinity by bonding two or more cellulose molecules by hydrogen bonds. In one embodiment, cellulose having such crystallinity can be used as a raw material. In this embodiment, it is preferable to use cellulose after reducing the crystallinity by performing a treatment for reducing the crystallinity, such as pre-disintegration, in order to increase the hydrolysis rate. The cellulose with reduced crystallinity may be cellulose whose crystallinity has been partially reduced or whose crystallinity has been completely or almost completely eliminated. There is no particular restriction on the method of the crystallinity reduction treatment, but it is preferable that the crystallinity reduction treatment is a treatment that can at least partially generate single-chain cellulose molecules by breaking the hydrogen bonds. By using cellulose containing at least partially single-chain cellulose molecules as a raw material, the efficiency of hydrolysis can be significantly improved.

[0025] Examples of the crystallinity reduction treatment of the raw cellulose include a method for obtaining single-chain cellulose molecules by physically breaking hydrogen bonds between cellulose molecules, such as a ball mill method for preliminary crushing (see Zhao et al., Energy & Fuels, 20, 807 (2006)), and a method for obtaining single-chain cellulose by chemically breaking hydrogen bonds between cellulose molecules without applying compressive shear stress, such as phosphoric acid treatment (see Zhang et al., Biomacromolecules, 7, 644 (2006)). The crystallinity reduction treatment of cellulose does not have to be a treatment that completely eliminates the crystallinity of cellulose, and may be a treatment that only partially reduces the crystallinity of cellulose before the treatment. By using cellulose that has been subjected to such treatment as the raw material, the efficiency of hydrolysis can be significantly improved.

[0026] Furthermore, examples of treatments for reducing the crystallinity of the raw cellulose include compressed hot water treatment (see, for example, Hayashi et al., J. Jpn. Inst. Energy, 83, 805 (2004); Sasaki et al., Ind. Eng. Chem. Res., 39, 2883 (2000)).

[0027] Xylan is a polysaccharide in which D-xylose residues are linked by β-1,4 or β-1,3 bonds. The sugars constituting xylan may include arabinose, glucuronic acid, 4-O-methylglucuronic acid, glucose, galactose, etc. in addition to xylose.

[0028] It is preferable to pre-disintegrate xylan by applying compressive shear stress before hydrolysis. A compressive shear type disintegrator can be used to disintegrate xylan by applying compressive shear stress. The compressive shear type disintegrator is a machine capable of applying both compressive stress and shear stress, and examples of such machines include a vibrating rod mill and a vibrating ball mill. Among these, a vibrating rod mill is preferable from the viewpoint of production efficiency. The rod is not particularly limited, but preferably has an outer diameter of 0.1 to 100 mm, more preferably 0.5 to 50 mm. The filling rate of the rod (apparent volume of the rod relative to the volume of the stirring part of the vibrating mill) varies depending on the model, but is preferably 10 to 97%, more preferably 15 to 95%.

[0029] The disintegration conditions, such as the disintegration time and the number of revolutions of the disintegrator, may be appropriately set to form a desired disintegrated product. From the viewpoint of obtaining a high hydrolysis rate, it is preferable that the crystallinity of the disintegrated xylan product is low.

[0030] Xylan may be coarsely pulverized before the preliminary disintegration by compressive shear stress. The method of coarsely pulverizing is not particularly limited, and for example, a cutter-type pulverizer such as a grinder / roll cutter, an impact pulverizer such as a hammer mill, or a grinding pulverizer such as a colloid mill can be used as a pulverizer.

[0031] In the cellulose-xylan mixture, the xylan content is 5-50% by mass relative to the total content of cellulose and xylan (100% by mass). By containing 5% by mass or more of xylan, the solubility of the hydrolysate in water is increased, and a cellooligosaccharide-containing composition with excellent storage stability can be produced. When the xylan content is 50% by mass or less, the target cellooligosaccharide-containing composition can be obtained in a sufficient yield. In the cellulose-xylan mixture, the xylan content is preferably 7-40% by mass, more preferably 10-30% by mass, and even more preferably 15-25% by mass relative to the total content of cellulose and xylan (100% by mass).

[0032] The xylan content in a cellulose-xylan mixture is determined by the method described in the Examples below. Specifically, the mixture used as the raw material is hydrolyzed to monosaccharide units using an aqueous sulfuric acid solution, etc., and the glucose and xylose contents in the product are analyzed to determine the xylan content relative to the total cellulose and xylan content (100% by mass) in the mixture used as the raw material. However, it is assumed that xylan is composed only of xylose.

[0033] The cellulose-xylan mixture may contain other components (e.g., other polysaccharides) in addition to cellulose and xylan. The amount of the other components is preferably 10% by mass or less, more preferably 5% by mass or less, based on 100% by mass of the mixture.

[0034] The cellulose and xylan contained in the cellulose-xylan mixture may be mixed before being put into the reactor for hydrolysis reaction, or may be mixed in the reactor for hydrolysis reaction. A commercially available product containing cellulose and xylan may be purchased and used as the cellulose-xylan mixture. For example, cellulose produced from cellulosic biomass containing a xylose skeleton in addition to a glucose skeleton may not have xylan completely removed and may be mixed into the cellulose. If the xylan content is 5 to 50 mass% relative to the total content of cellulose and xylan (100 mass%), such commercially available cellulose can be used as the cellulose-xylan mixture.

[0035] <Hydrolysis reaction> In one embodiment of the method for producing a cellooligosaccharide-containing composition, a cellulose / xylan mixture is hydrolyzed in the presence of an acid catalyst to produce cellooligosaccharides.

[0036] As the acid catalyst, a conventionally known acid can be used. Specifically, at least one acid selected from the group consisting of sulfuric acid, sulfurous acid, hydrochloric acid, perchloric acid, nitric acid, nitrous acid, and phosphoric acid, or a partially neutralized salt thereof can be used. Examples of the partially neutralized salt of the acid include monopotassium dihydrogen phosphate, monoammonium dihydrogen phosphate, and potassium hydrogen sulfate. The acid catalyst is preferably phosphoric acid or a partially neutralized salt thereof, and more preferably phosphoric acid.

[0037] The amount of acid catalyst used is preferably such that the mass ratio of the cellulose / xylan mixture to the acid catalyst is (cellulose / xylan mixture) / (acid catalyst) = 2 to 100, more preferably (cellulose / xylan mixture) / (acid catalyst) = 4 to 20, and even more preferably (cellulose / xylan mixture) / (acid catalyst) = 5 to 12. When the mass ratio of the cellulose / xylan mixture to the acid catalyst is 100 or less, hydrolysis proceeds at a rate that is practically problem-free. When the mass ratio of the cellulose / xylan mixture to the acid catalyst is 2 or more, side reactions such as dehydration reactions and cleavage of carbon-carbon bonds during hydrolysis can be suppressed.

[0038] The mass of the cellulose-xylan mixture in this disclosure is the true mass (dry mass) excluding the moisture contained in the raw material. Since cellulose and xylan usually contain physically adsorbed moisture, the amount of attached moisture is analyzed, and the mass ratio of the cellulose-xylan mixture to the acid catalyst is calculated based on the mass of the cellulose-xylan mixture excluding the moisture. One method for analyzing the amount of attached moisture is to place the cellulose-xylan mixture used as the raw material in a thermostatic dryer at 100°C to 150°C, dry it until there is no mass loss, and then quantify it. In order to prevent the effects of side reactions such as dehydration reactions during drying, it is more desirable to dry it at a lower temperature using a vacuum dryer and then quantify it. The mass of the acid catalyst is also the true mass (dry mass) of the acid catalyst.

[0039] As mentioned above, the cellulose-xylan mixture before hydrolysis already contains about 1-12% by mass of physically adsorbed water. In addition, many acid catalysts such as hydrochloric acid and phosphoric acid contain water in their normal commercial form. Therefore, hydrolysis can proceed without adding water, using the water physically adsorbed in the cellulose-xylan mixture and the water contained in the acid catalyst. Usually, the amount of water is sufficient without adding water, but for cellulose-xylan mixtures that are very dry, water can be added to perform hydrolysis.

[0040] Whether water is added or not, the cellulose-xylan mixture contains about 1 to 12% by mass of physically adsorbed water. Therefore, the amount of water in the hydrolysis reaction, including the amount of water physically adsorbed in the cellulose-xylan mixture and the water contained in the acid catalyst, and the amount of water added when water is added, is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 8 parts by mass, per 100 parts by mass of the true cellulose-xylan mixture (dry mass). When it is 15 parts by mass or less, a sufficient hydrolysis rate can be obtained and inoperability due to adhesion to the device can be prevented. Also, when it is 0.1 parts by mass or more, side reactions such as dehydration reactions can be suppressed.

[0041] In one embodiment of the method for producing a cellooligosaccharide-containing composition, it is preferable to use a method for hydrolyzing a cellulose / xylan mixture by applying a mechanical external force through a crushing treatment (mechanochemical method).

[0042] Examples of grinding equipment used in the grinding process include tumbling ball mills such as pot mills, tube mills, and conical mills; jet grinders such as swirling flow jet mills, collision type jet mills, fluidized bed jet mills, and wet type jet mills; shear mills such as mortars and ong mills; colloid mills such as mortars and stone mortars; impact grinders such as hammer mills, cage mills, pin mills, disintegrators, screen mills, turbo mills, and centrifugal classifier mills; vibration mills that grind materials by vibrating a drum to move the media inside; stirring mills that place media and raw materials in a can body with stirring blades and grind them by rotating them; and planetary ball mills, which are grinders that employ rotation and revolution motion.

[0043] The grinding device is preferably a ball mill, a vibration mill, or a stirring mill, which applies a strong compressive force to the cellulose-xylan mixture and a tensile stress in both directions of the main chain. The grinding device is more preferably a planetary ball mill, a rolling ball mill, a vibration mill, or a stirring mill, and further preferably a planetary ball mill or a vibration mill.

[0044] At the laboratory level, it is preferable to use a planetary ball mill. Industrially, it is preferable to use a vibration mill. A vibration mill does not rotate a drum (grinding tube) in which the grinding media is inserted, but rather vibrates the drum to move the media inside, making it possible to grind in about 1 / 10 to 1 / 20 of the time required by a drum rotary ball mill. A stirring mill does not rotate the drum, but rather rotates the stirring blades to move the media, making it possible to grind in about 1 / 10 to 1 / 20 of the time required by a drum rotary ball mill.

[0045] The pulverization process can be carried out continuously or intermittently. In order to suppress the temperature rise of the object to be treated accompanying the pulverization process, it is preferable to carry out the pulverization process intermittently. When the pulverization process is carried out intermittently, the optimum value varies greatly depending on the pulverization device, but for example, in the case of a planetary ball mill, it can be carried out by repeating a cycle of 5 to 15 minutes of pulverization process with an interval of 5 to 15 minutes between each pulverization process. When the pulverization process is carried out continuously, it is preferable to carry out the pulverization process while maintaining the temperature at an appropriate level by installing a jacket or the like on the pulverization device to cool it.

[0046] When a cellulose-xylan mixture is hydrolyzed using a grinding device such as a ball mill, the crystallinity of cellulose or xylan can be reduced by grinding, or the crystallinity of cellulose or xylan can be reduced in advance as described above, and then hydrolysis can be performed by adding an acid catalyst. When cellulose or xylan is pre-grinded using a Henschel mixer and then ground using a ball mill, the acid catalyst can be added from the pre-grinding stage.

[0047] In one embodiment of the method for producing a cellooligosaccharide-containing composition, when hydrolysis is performed without a grinding treatment, examples of the method that does not involve grinding include a method of kneading using a pressure kneader and a method of reacting using an extrusion molding machine after kneading in a kneader.

[0048] The hydrolysis temperature is preferably room temperature to 110°C, more preferably 50°C to 100°C. If the temperature is above room temperature, the decomposition does not slow down, and the time required for decomposition does not become too long. In order to accelerate the decomposition rate, the hydrolysis can be performed at a high temperature. If the hydrolysis temperature is 110°C or less, side reactions such as dehydration reactions can be suppressed. Depending on the reaction device, shear heat generation may be large, so it is preferable to repeat cycles with intervals as described above, or to run cooling water through the jacket of the reaction device to control the hydrolysis temperature.

[0049] The hydrolysis time depends on the reaction apparatus used, but is generally preferably 2 to 150 hours, more preferably 5 to 80 hours, even more preferably 10 to 60 hours, and particularly preferably 15 to 40 hours. When the hydrolysis time is 2 hours or more, the decomposition of the cellulose-xylan mixture is promoted. When the hydrolysis time is 150 hours or less, the hydrolyzate can be obtained more efficiently. In the present disclosure, when hydrolysis is performed by a crushing process and the crushing process is performed intermittently, the hydrolysis time refers to the net crushing process time excluding the interval.

[0050] The progress of hydrolysis of a cellulose-xylan mixture can be monitored by sampling small amounts of the material over time and measuring the amount of water-soluble components contained in the samples.

[0051] <Other processes> In one embodiment, the method for producing a cellooligosaccharide-containing composition may include the following steps as necessary in addition to the step of carrying out the hydrolysis reaction described above.

[0052] [Extraction process] In one embodiment, the method for producing a cellooligosaccharide-containing composition may include a step of adding water to the reaction product after the hydrolysis reaction to extract the water-soluble components. When the amount of water used during hydrolysis is small, the reaction product is in a solid form, and it is preferable to carry out an extraction step.

[0053] The mass ratio of the amount of water added to the reactants is preferably (amount of water added) / (reactants)=0.5 to 100, more preferably 1 to 20, and even more preferably 2 to 10. When the mass ratio is 0.5 or more, the soluble components in the reactants can be efficiently dissolved, and when the mass ratio is 100 or less, the container for dissolution does not become too large, which is efficient.

[0054] The water to be added to the reaction product is not particularly limited, but distilled water is usually used. In addition to distilled water, a solution containing a salt, a buffer solution, etc. may be used. An organic solvent miscible with water may also be added to the extent that it does not affect the dissolution of the soluble components in the reaction product.

[0055] The separation of the water-soluble component and the solid component can be carried out by a method generally used for removing solids from a suspension, for example, filtration can be carried out using filter paper, filter cloth, a membrane filter, a filter press, a centrifugal filter, a cross-flow filter, etc., or natural sedimentation or centrifugal sedimentation can be carried out.

[0056] In order to obtain cellooligosaccharides with high purity, a purification procedure may be performed in which solids are removed from the reaction product, ethanol or the like is added to an aqueous solution containing water-soluble components to reprecipitate cellooligosaccharides, the resulting precipitate is dissolved again in water, and the ethanol reprecipitation is repeated.

[0057] [Neutralization process] In one embodiment, the method for producing a cellooligosaccharide-containing composition may include a step of neutralizing the reaction product by adding a basic compound after the hydrolysis reaction. Since the reaction product obtained by the hydrolysis reaction contains the acid catalyst used in the hydrolysis, the acid catalyst can be neutralized by adding a basic compound.

[0058] When the above-mentioned extraction step is carried out after the hydrolysis reaction, the neutralization step may be carried out after the extraction step or simultaneously with the extraction step.

[0059] The basic compound is preferably at least one selected from the group consisting of potassium salts, phosphates, ammonium salts, and ammonia.

[0060] When a potassium salt is used as the basic compound, for example, potassium hydroxide, potassium carbonate, potassium formate, potassium acetate, potassium ethoxide, monopotassium dihydrogen phosphate, dipotassium monohydrogen phosphate, tripotassium phosphate, potassium amide, etc. Among these, potassium hydroxide, potassium carbonate, dipotassium monohydrogen phosphate, and tripotassium phosphate are preferred.

[0061] When a phosphate is used as the basic compound, it is possible to use monopotassium dihydrogen phosphate, dipotassium monohydrogen phosphate, tripotassium phosphate, diammonium hydrogen phosphate, triammonium phosphate, etc. Thus, the phosphate may be a potassium salt or an ammonium salt at the same time.

[0062] When an ammonium salt is used as the basic compound, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium carbonate, diammonium hydrogen phosphate, triammonium phosphate, ammonium nitrate, ammonium sulfate, etc. can be used. Among these, diammonium hydrogen phosphate and ammonium sulfate are preferred.

[0063] When ammonia is used as the basic compound, it is preferable to use aqueous ammonia.

[0064] The temperature of the neutralization reaction is preferably 0°C to 50°C, more preferably 5°C to 40°C, and even more preferably 20°C to 30°C in order to prevent the product of the hydrolysis reaction from reacting excessively. The neutralization reaction itself is fast, but when insoluble matter derived from the raw material is present, it is necessary to sufficiently diffuse the acid, so the time of the neutralization reaction is preferably 0.1 hours to 10 hours, more preferably 0.5 hours to 5 hours, and even more preferably 1 hour to 3 hours. There is no need for a special device to be used for the neutralization reaction, and a normal stirring tank can be used. When hydrochloric acid or sulfuric acid is used as the acid catalyst, it is preferable to use a stirring tank lined with a corrosion-resistant material such as glass.

[0065] When the neutralization step is performed, since a precipitate may be formed by bringing the pH to the neutral side, it is preferable to separate the solid content by filtration after the neutralization reaction. When filtration is performed after the neutralization reaction, the operation of separating (filtering) the water-soluble component from the solid component after extracting the water-soluble component in the above extraction step can be omitted.

[0066] The separation of the solid content after the neutralization reaction can be carried out by a method generally used for removing solid content from a suspension, for example, filtration can be carried out using filter paper, filter cloth, membrane filter, filter press, centrifugal filter, cross-flow filter, etc., or natural sedimentation or centrifugal sedimentation can also be carried out.

[0067] <Products of hydrolysis reaction> Known methods for producing a cellooligosaccharide-containing composition by hydrolysis of cellulose include a carbon catalyst method and an acid catalyst method.

[0068] The carbon catalyst method is a method in which cellulose is hydrolyzed in the presence of a carbon catalyst such as activated carbon and water. In this method, only linear cellooligosaccharides are produced, as shown in the following formula (1).

[0069] [ka] (In formula (1), m and n represent the degree of polymerization.)

[0070] The acid catalyst method is a method in which cellulose is hydrolyzed in the presence of an acid catalyst. In this method, in addition to the reaction shown in formula (1) above, a reaction to produce branched cellooligosaccharides also occurs, as shown in formula (2) below. That is, cellooligosaccharides having a branched skeleton can be produced by reacting the hydroxyl group at the 6-position with cellulose. Such branched products have higher solubility in water than linear products.

[0071] [ka] (In formula (2), m, n, x, and y represent the degree of polymerization.)

[0072] In one embodiment of the method for producing a cellooligosaccharide-containing composition, a cellulose-xylan mixture containing a predetermined ratio of xylan is used as a raw material for the reaction in an acid catalyst method. Without being bound by any theory, in this reaction, as shown in the following formula (3), the hydroxyl group at the 6-position also reacts with xylan (or xylose, which is a hydrolysis product of xylan, not shown in formula (3)), and a branched cellooligosaccharide in which a xylan residue (or a xylose residue) is incorporated into the cellulose skeleton can be produced. It is presumed that such a branched cellooligosaccharide in which a xylan residue or a xylose residue is incorporated has even higher solubility in water.

[0073] [ka] (In formula (3), m, n, x, and y represent the degree of polymerization.)

[0074] Although the details are not clear, in one embodiment of the method for producing a cellooligosaccharide-containing composition, it is presumed that the solubility in water is increased by producing some branched cellooligosaccharides incorporating xylan residues or xylose residues as described above, thereby suppressing the occurrence of turbidity in an aqueous cellooligosaccharide solution and improving storage stability.

[0075] The number average molecular weight of the cellooligosaccharide produced by the method for producing a cellooligosaccharide-containing composition of one embodiment is preferably 340 to 1640, more preferably 420 to 1320, and even more preferably 500 to 990. The number average molecular weight of the cellooligosaccharide is determined by the method described in the Examples below. When the cellooligosaccharide contains a xylose unit, the number average molecular weight of the cellooligosaccharide is the molecular weight including the xylose unit.

[0076] The ratio of α-1,6-glycosidic bonds to the total polymeric bonds of the cellooligosaccharide produced by the method for producing a cellooligosaccharide-containing composition of one embodiment (hereinafter, sometimes referred to as the "branching degree" of the cellooligosaccharide) is preferably 1 to 50%, more preferably 3 to 40%, even more preferably 5 to 30%, and particularly preferably 5 to 20%. The "polymeric bond" in cellooligosaccharide refers to a bond that links monosaccharides to form an oligosaccharide, typically a glycosidic bond. The branching degree is determined from the area ratio of the NMR spectrum by the method described in the Examples below. The branching degree is a value including the ratio of α-1,6-glycosidic bonds incorporating xylan residues or xylose residues as represented by the above formula (3). EXAMPLES

[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0078] <1. Analysis of raw materials> The polysaccharides used as raw materials were hydrolyzed to monosaccharide units by the following method, and the composition of the raw materials was analyzed.

[0079] 100 mg of polysaccharide was mixed with 1 mL of 72% by mass aqueous sulfuric acid solution and stirred for 1 hour at 30° C. Then, 28 mL of water was added to the mixture, which was stirred for 1 hour at 120° C., cooled, and filtered. The obtained filtrate was analyzed by HPLC to determine the glucose content and xylose content in the filtrate.

[0080] [HPLC analysis conditions] Column: Shodex (registered trademark) GF-210 (manufactured by Showa Denko K.K.) x 3 Eluent: 0.2M acetic acid aqueous solution Column temperature: 40℃ Eluent flow rate: 0.6mL / min Detector: Differential refractive index detector

[0081] The composition of the polysaccharides used as the raw material was determined from the glucose and xylose contents determined by HPLC analysis. It was assumed that xylan consisted only of xylose. The results are shown below. Cellulose Arbocel B600 (Rettenmeyer): 80% by mass cellulose, 20% by mass xylan Avicel (Merck crystalline cellulose powder): 99% by mass cellulose, 1% by mass xylan Xylan (Sigma-Aldrich, birch wood xylan): 100% xylan by mass

[0082] <2. Production of oligosaccharides> [Example 1] Production of cellooligosaccharide-containing composition using cellulose (Arbocel) as raw material by acid catalysis

[0083] Cellulose Arbocel B600 (manufactured by Rettenmeyer) was used as the raw material mixture.

[0084] 3.79 kg of the above raw material mixture (moisture content 3.4% by mass, dry mass 3.66 kg, xylan content: 20% by mass) was mixed with 0.53 kg of 85% aqueous phosphoric acid solution (special grade reagent, Fujifilm Wako Pure Chemical Industries, Ltd.) using a Henschel mixer (apparatus name: FM20C / I, manufactured by Nippon Coke and Engineering Co., Ltd.). The mass ratio of the cellulose-xylan mixture to the acid catalyst was (cellulose-xylan mixture) / (acid catalyst) = 8.1. The mixing conditions were a rotation speed of 1400 rpm and aeration of 0.4 m. 3 / Hr.

[0085] 350 g of this mixture was transferred to a vibration mill (device name: MB-1 type, manufactured by Chuo Kakoki Co., Ltd.) and hydrolysis was carried out while pulverizing at 75° C. for 72 hours. The pulverization conditions were a total amplitude of 8 mm, a rotation speed of 1000 rpm, and a φ3 / 4 inch carbon steel ball.

[0086] The pulverized material was removed from the vibration mill and separated from the balls, and 300 g of the pulverized material was transferred to a dissolving device (5 L container). 2817 g of ion-exchanged water was added, and the mixture was stirred for 1 hour at 25°C using a Three-One Motor (registered trademark). This allowed the water-soluble components to dissolve, and a hydrolyzate extract was obtained.

[0087] To this extract, 61 g of a 48% potassium hydroxide aqueous solution was added, and the mixture was stirred for 1 hour at 25° C. using a three-one motor. 122 g of perlite #31 (Showa Chemical Industry Co., Ltd.) was added as a filter aid, and the mixture was filtered using a pressure filter (KST-293-20, Advantec Toyo Co., Ltd.) to obtain 2,533 g of filtrate.

[0088] The filtrate had a pH of 6.8, and was hydrolyzed with sulfuric acid in the same manner as in the analysis of the raw material, and the monomers were analyzed by HPLC. As a result, it was found to contain 167 g of cellulose hydrolysate and 42 g of xylan hydrolysate.

[0089] The obtained filtrate was diluted with water so that the sugar concentration (total concentration of cellulose hydrolysate and xylan hydrolysate) became 5 mass %, and used as a sample solution for the turbidity measurement described below.

[0090] The number average molecular weight and the degree of branching of the hydrolysate in the filtrate were determined by the following method. Note that the xylan hydrolysate contained in the filtrate was not separated when the measurements were performed.

[0091] [Method of analyzing number average molecular weight] The number average molecular weight was determined by GPC (gel permeation chromatography) analysis using an HPLC (high performance liquid chromatogram) apparatus.

[0092] Each sample prepared under the conditions shown in Table 1 was irradiated with ultrasonic waves for 5 minutes to disperse and dissolve the sample, which was then left to stand overnight and then filtered through a 0.45 μm PTFE membrane filter (model number 25HP045AN, manufactured by Advantec Toyo Co., Ltd.) to prepare a standard sample. "Standard 1" and "Standard 2" were used for the analysis of cellooligosaccharides. In Table 1, "Mp" represents the peak top molecular weight.

[0093] Analytical samples were prepared by diluting 0.10 g of each filtrate into 1 g of water.

[0094] [Table 1]

[0095] The analytical equipment used was a GPC-LS (Agilent, 1260 Infinity), and measurements were performed under the following analytical conditions to determine the number average molecular weight of all peaks of each analytical sample. (Analysis conditions) Column: Shodex (registered trademark) SB-G 6B (guard column) + SB802.5HQ (analytical column) x 3 Column temperature: 40℃ Eluent: 30v / v% acetonitrile + 70v / v% water 0.2M acetic acid aqueous solution Flow rate: 0.5mL / min Injection volume: 20μL Detector: Differential refractometer (RI)

[0096] [Method of branching analysis] The branching degree was determined using an NMR (nuclear magnetic resonance) device under the following conditions. (NMR conditions) Equipment:Bruker AVANCE 500(500MHz) Measurement method: 1 H-NMR, 13 C-NMR, 13 C-DEPT135, HSQC Lock solvent: D 2 O Internal standard:TSP-d 4(Sodium trimethylsilylpropionate) = 0 ppm Temperature: room temperature Sample preparation: Powder sample (50 mg) / D 2 O(1mL)+TSP-d 4 (5mg)

[0097] The filtrate was vacuum dried in advance to prepare a powder sample, and the measurement sample was prepared as follows. 50 mg of the powder sample was precisely weighed and placed in a 50 mL sample bottle. 2 After adding 1 mL of O2 and dissolving, the mixture was shaken in an ultrasonic cleaner for 5 minutes, and then dried in a vacuum dryer (30°C). The amount of water removed was calculated by weighing again. 4 (5mg) and D 2 O (1 mL) was added again, and the mixture was shaken in an ultrasonic cleaner for 5 minutes. The mixture was then filtered through a 0.45 μm disposable filter (model number: 25HP045AN, manufactured by Advantec Toyo Co., Ltd.) and sealed in a 5 mmφ NMR sample tube. NMR measurement was performed immediately after sampling.

[0098] The branching degree was calculated using the following formula based on the area ratio of the spectrum of "α-1,6-H1" detected at 4.9 to 5.0 ppm and the spectrum of "β-1,4-H1" detected at 4.4 to 4.6 ppm. Branching degree = (α-1,6-H1)÷[(α-1,6-H1)+(β-1,4-H1)]×100(%)

[0099] The number average molecular weight of the hydrolyzate produced in Example 1 was 800 (the number average degree of polymerization converted to glucose units was 4.8), and the branching degree was 14%. 1 The H-NMR spectrum is shown in Figure 1.

[0100] [Example 2] Production of cellooligosaccharide-containing composition using cellulose (Avicel) and xylan as raw materials by acid catalysis Hydrolysis reaction, extraction of the hydrolyzate, and filtration of the extract were performed in the same manner as in Example 1, except that 3.02 kg of Avicel (crystalline fine cellulose manufactured by Merck) (moisture content 3.1% by mass, dry mass 2.93 kg) and 0.81 kg of xylan (manufactured by Sigma-Aldrich, birch wood-derived xylan) (moisture content 9.8% by mass, dry mass 0.73 kg) were used as the raw material mixture (xylan content: 21% by mass). The mass ratio of the cellulose-xylan mixture to the acid catalyst was (cellulose-xylan mixture) / (acid catalyst) = 8.1.

[0101] The filtrate had a pH of 6.8, and was hydrolyzed with sulfuric acid in the same manner as in the analysis of the raw material, and the monomers were analyzed by HPLC. As a result, it was found to contain 166 g of cellulose hydrolysate and 42 g of xylan hydrolysate.

[0102] The obtained filtrate was diluted with water so that the sugar concentration (total concentration of cellulose hydrolysate and xylan hydrolysate) became 5 mass %, and used as a sample solution for the turbidity measurement described below.

[0103] The number average molecular weight and branching degree of the hydrolysate in the filtrate were determined by the method described in Example 1. As a result, the number average molecular weight was 780 (number average degree of polymerization converted to glucose units was 4.7), and the branching degree was 18%. 1 The H-NMR spectrum is shown in Figure 2.

[0104] [Comparative Example 1] Production of cellooligosaccharide-containing composition using cellulose (Avicel) as raw material by acid catalysis Except for using 3.91 kg (water content 3.1%, dry mass 3.79 kg) of Avicel (crystalline fine cellulose manufactured by Merck) as the raw material, hydrolysis reaction, extraction of the hydrolyzate, and filtration of the extract were performed in the same manner as in Example 1 to obtain a filtrate. The mass ratio of the cellulose-xylan mixture to the acid catalyst was (cellulose-xylan mixture) / (acid catalyst) = 8.4.

[0105] The filtrate had a pH of 6.8, and was hydrolyzed with sulfuric acid in the same manner as in the analysis of the raw material, and the monomer was analyzed by HPLC, which revealed that it contained 207 g of cellulose hydrolysate. The obtained filtrate was diluted with water to a sugar concentration (concentration of cellulose hydrolysate) of 5 mass%, and used as a sample solution for the turbidity measurement described below.

[0106] The number average molecular weight and branching degree of the hydrolysate in the filtrate were determined by the method described in Example 1. As a result, the number average molecular weight was 810 (number average degree of polymerization converted to glucose units was 4.9), and the branching degree was 12%. 1 The H-NMR spectrum is shown in Figure 3.

[0107] [Comparative Example 2] Production of cellooligosaccharide-containing composition using cellulose (Avicel) as raw material by carbon catalyst method 10 g of Avicel (crystalline fine cellulose manufactured by Merck) and 1.5 g of activated carbon BA50 (manufactured by Ajinomoto Fine-Techno Co., Ltd.) were placed in a 3600 mL ceramic pot mill together with 2000 g of alumina balls with a diameter of 1.5 cm, and set on a tabletop pot mill rotating platform (manufactured by Nitto Kagaku Co., Ltd., tabletop pot mill model ANZ-51S), and treated at 60 rpm for 48 hours to obtain the reaction raw material. The temperature was started at room temperature, and the temperature rise due to shear heat generation was allowed to proceed naturally.

[0108] Next, 0.374 g of the reaction raw materials and 40 mL of water were placed in a high-pressure reactor (inner volume 100 mL, autoclave manufactured by OM Labotec Co., Ltd., made of Hastelloy C22), and then heated to the reaction temperature of 230°C at a rate of 10 to 30°C / min (average heating rate 11.3°C / min) while stirring at 600 rpm. Heating was then immediately stopped, and the reactor was cooled by air cooling at a rate of 10 to 30°C / min (average cooling rate 16.7°C / min) to produce a reaction liquid.

[0109] The reaction solution was then centrifuged to recover the supernatant, which was then freeze-dried to obtain a cellooligosaccharide powder. The resulting powder was dissolved in water to a sugar concentration (cellulose hydrolysate concentration) of 5% by mass, and used as a sample solution for the turbidity measurement described below.

[0110] The number average molecular weight and branching degree of the hydrolysate were determined by the method described in Example 1. As a result, the number average molecular weight was 780 (number average degree of polymerization converted to glucose units was 4.7), and the branching degree was 0%. 1 The H-NMR spectrum is shown in Figure 4.

[0111] <3. Observation of the presence or absence of turbidity and measurement of turbidity> The sample solutions obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were observed for the presence or absence of turbidity and their turbidity was measured immediately after preparation and after storage for 7 days. The results are shown in Table 2.

[0112] The sample solution was stored by filling 40 mL of the sample solution into a 50 mL glass screw-cap bottle and leaving it to stand in a thermostatic bath set at 30°C.

[0113] The turbidity was measured using the following method. A fully dispersed sample solution (sample 1) and a sample solution (sample 2) obtained by filtering sample 1 through a 0.45 μm membrane were prepared, and each sample was placed in a 1 cm square cell and the absorbance at a wavelength of 660 nm was measured. The turbidity was calculated from the measured absorbance using the following formula. Turbidity = (absorbance of sample 1) - (absorbance of sample 2)

[0114] [Table 2]

[0115] The results in Table 2 show that in Examples 1 and 2, in which a cellulose-xylan mixture containing a specified ratio of xylan was used as the raw material, the sample solution did not become cloudy even after 7 days of storage, demonstrating excellent storage stability. On the other hand, in Comparative Example 1, in which cellulose containing almost no xylan was used as the raw material, cloudiness occurred after 7 days of storage, and in Comparative Example 2, cloudiness occurred immediately after preparation. [Industrial Applicability]

[0116] According to the method for producing a cellooligosaccharide-containing composition of the present invention, a cellooligosaccharide-containing composition having excellent storage stability even if it has a relatively high degree of polymerization can be produced.

Claims

1. A method for producing a cellooligosaccharide-containing composition, comprising hydrolyzing a raw material mixture containing cellulose and xylan in the presence of an acid catalyst, wherein the raw material mixture contains 5 to 50% by mass of the xylan relative to a total content of the cellulose and the xylan of 100% by mass.

2. 2. The method for producing a cellooligosaccharide-containing composition according to claim 1, wherein the raw material mixture contains 7 to 40% by mass of the xylan relative to a total content of the cellulose and the xylan of 100% by mass.

3. 3. A method for producing a cellooligosaccharide-containing composition according to claim 1, wherein the acid catalyst is at least one acid selected from the group consisting of sulfuric acid, sulfurous acid, hydrochloric acid, perchloric acid, nitric acid, nitrous acid, and phosphoric acid, or a partially neutralized salt thereof.

4. The method for producing a cellooligosaccharide-containing composition according to claim 3, wherein the acid catalyst is phosphoric acid or a partially neutralized salt thereof.

5. The method for producing a cellooligosaccharide-containing composition according to claim 4, wherein the acid catalyst is phosphoric acid.

6. A method for producing a cellooligosaccharide-containing composition according to any one of claims 1 to 5, comprising hydrolyzing the raw material mixture by grinding in the presence of the acid catalyst.

7. The method for producing a cellooligosaccharide-containing composition according to claim 6, wherein the grinding treatment is carried out using a planetary ball mill or a vibrating mill.

Citation Information

Patent Citations

  • Method for decreasing molecular weight of cellulose and method for producing saccharide using the same

    JP2006320261A

  • Method for producing cellulase and cellooligosaccharide

    JP2009189293A

  • METHOD FOR PRODUCING beta-GLUCANASE AND XYLANASE WITH WHEAT BRAN AND LIQUID CULTURE MEDIUM

    JP2011041522A

  • Apparatus and method for treating biomass

    JP2011068578A

  • Method of producing oligosaccharide

    JP2013063051A